Prediction of Fatigue Life of a Continuous Bridge Girder Based on Vehicle Induced Stress History. (2003) - Rao, V.G.; Talukdar, S.
Abstract : The fatigue damage assessment of bridge components by conducting a full scale fatigue testing is often prohibitive. A need, therefore, exists to estimate the fatigue damage in bridge components by a simulation of bridge-vehicle interaction dynamics due to the action of the actual traffic. In the present paper, a systematic method has been outlined to find the fatigue damage in the continuous bridge girder based on stress range frequency histogram and fatigue strength parameters of the bridge materials. Vehicle induced time history of maximum flexural stresses has been obtained by Monte Carlo simulation process and utilized to develop the stress range frequency histogram taking into consideration of the annual traffic volume. The linear damage accumulation theory is then applied to calculate cumulative damage index and fatigue life of the bridge. Effect of the bridge span, pavement condition, increase of vehicle operating speed, weight and suspension characteristics on fatigue life of the bridge have been examined.